Mixed convection in MHD flow and heat transfer rate near a stagnation-point on a non-linear vertical stretching sheet - Fenuga, Olugbenga John; Hassan, Anthony R.; Olanrewaju, Philip Oladapo (Zielona Góra: Uniwersytet Zielonogórski)
This work investigates the mixed convection in a Magnetohydrodynamic (MHD) flow and heat transfer rate near a stagnation-point region over a nonlinear vertical stretching sheet. Using a similarity transformation, the governing equations are transformed into a system of ordinary differential equations which are solved numerically using the fourth order Runge-Kutta method with shooting technique.
Keywords: mixed convection; MHD flow; heat transfer rate; stagnation -point; non-linear vertical stretching sheet